2015
DOI: 10.1002/jwmg.1010
|View full text |Cite
|
Sign up to set email alerts
|

Allegheny woodrat hard mast preference and response to food supplementation

Abstract: Range-wide declines of the Allegheny woodrat (Neotoma magister) have been attributed, in part, to reductions in mast associated with extirpation of American chestnut (Castanea dentata) and transition to oak (Quercus)-dominated forests prone to periodic mast failure. Chestnuts produce mast more consistently than oaks; hence, efforts to restore a blight-resistant hybrid chestnut may facilitate woodrat recovery. Our goal was to describe the implications of chestnut restoration for imperiled Allegheny woodrat popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Both methods have the advantage of directly confirming presence without having to restrain animals. Cameras have been used to investigate woodrat behavior in natural settings (Morton and Pereyra , Stovall and Hayslette , Smyser et al , Cove et al ). Castleberry et al () demonstrated that cameras were effective to detect Allegheny woodrats ( N. magister ) over bait at locations with woodrat sign, immediately following woodrat captures at the location.…”
mentioning
confidence: 99%
“…Both methods have the advantage of directly confirming presence without having to restrain animals. Cameras have been used to investigate woodrat behavior in natural settings (Morton and Pereyra , Stovall and Hayslette , Smyser et al , Cove et al ). Castleberry et al () demonstrated that cameras were effective to detect Allegheny woodrats ( N. magister ) over bait at locations with woodrat sign, immediately following woodrat captures at the location.…”
mentioning
confidence: 99%